2016
DOI: 10.1007/s10815-016-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Human embryo mosaicism: did we drop the ball on chromosomal testing?

Abstract: There are newly recognized challenges presented by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, our data can not necessarily be generalized, because it has been documented that there could be significant variability introduced by iatrogenic factors, such as the excessive force during the biopsy process, or the presence of dead or apoptotic cells could lead to artifactual loss or gain of chromosomes (23). Finally, questions persist regarding the technical limitations that may affect the diagnostic accuracy of mosaicism detection with currently available NGS-PGS platforms, challenging the interpretation of these findings (11,34,36). It has been suggested that the highest level of evidence of mosaicism would be demonstrated from reciprocal errors found in double biopsies of a blastocyst (37).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, our data can not necessarily be generalized, because it has been documented that there could be significant variability introduced by iatrogenic factors, such as the excessive force during the biopsy process, or the presence of dead or apoptotic cells could lead to artifactual loss or gain of chromosomes (23). Finally, questions persist regarding the technical limitations that may affect the diagnostic accuracy of mosaicism detection with currently available NGS-PGS platforms, challenging the interpretation of these findings (11,34,36). It has been suggested that the highest level of evidence of mosaicism would be demonstrated from reciprocal errors found in double biopsies of a blastocyst (37).…”
Section: Discussionmentioning
confidence: 90%
“…Ratios >80% or <20% can not be detected in a five-cell sample, but it is generally agreed that results beyond those ranges can be considered to be aneuploid or euploid, respectively (6,12). However, it has been suggested that under certain conditions, the finding of mosaicism may be artifactual or limited by a high false positive rate (11,34). Segmental aneuploidies and mosaicisms detected with the use of NGS have been confirmed with whole-blastocyst FISH analysis (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some cycles do not yield any embryos classified as euploid. This fact, coupled with the low incidence of monosomic mosaicism in prenatal specimens and liveborns, led to the proposal to transfer embryos demonstrating lethal autosomal monosomies on PGT‐A when no documented euploid embryos are available . Despite a paucity of published data regarding fetal and neonatal outcome of pregnancies resulting from such transfers, a recent survey suggests that the practice has rapidly gained acceptance by physicians performing IVF …”
Section: Introductionmentioning
confidence: 99%
“…A recent RCT showed that embryos cultured at 37°C have higher blastulation rates (60.1 vs. 51.6 %, p 0.03) and form more usable blastocysts (48.1 vs. 41.2 %, p 0.03) when compared to embryos cultured at 36°C [13], indicating the need for strictly controlled temperature of incubators and heated surfaces in the laboratory. If we follow this same principle, variations in the biopsy technique such as location of biopsy in the trophectoderm, due to segregation of abnormal cell lines, and/or number of cells removed, may impact the level of mosaicism reported [14]. We know that controlling for these variables by strict adherence to protocols and training of staff lead to comparable and reproducible outcomes with no difference in aneuploidy rates [15].…”
mentioning
confidence: 99%